A genetic score for the prediction of beta-thalassemia severity - Fabrice Danjou; Marcella Francavilla; Franco Anni; Stefania Satta; Franca-Rosa Demartis; Lucia Perseu; Matteo Manca; Maria Carla Sollaino; Laura Manunza; Elisabetta Mereu; Giuseppe Marceddu; Serge Pissard; et al. (Haematologica, 2015)
Clinical and hematologic characteristics of beta(β)-thalassemia are determined by several factors resulting in a wide spectrum of severity. Phenotype modulators are: HBB mutations, HBA defects and fetal hemoglobin production modulators (HBG2:g.−158C>T polymorphism, HBS1L-MYB intergenic region and the BCL11A). We characterized 54 genetic variants at these five loci robustly associated with the amelioration of beta-thalassemia phenotype, to build a predictive score of severity using a representative cohort of 890 β-thalassemic patients. Using Cox proportional hazard analysis on a training set, we assessed the effect of these loci on the age at which patient started regular transfusions, built a Thalassemia Severity Score, and validated it on a testing set. Discriminatory power of the model was high (C-index=0.705; R2=0.343) and the validation conducted on the testing set confirmed its predictive accuracy with transfusion-free survival probability (P